Penerapan Akuntansi Pertanggungjawaban sebagai Alat Penilaian Kinerja Manajer Pusat Biaya pada PT. Semen Indonesia Logistik - Nabilah Nur Fauziah; Anwar Hariyono (Jurnal Riset Akuntansi, 2025)
PT. Semen Indonesia Logistik, as a logistics service provider company, plays a strategic role in supporting Indonesia's economic dynamics. This research aims to determine the extent to which responsibility accounting is implemented as a tool to assess the performance of cost center managers at PT. Semen Indonesia Logistik in supporting the achievement of company objectives. Responsibility accounting is one of the most important components of overall control in a company. This research uses a qualitative descriptive method with a case study approach. The analysis results show that PT. Semen Indonesia Logistik has implemented responsibility accounting optimally. This can be seen from the responsibility accounting requirements that have been implemented, including the organizational structure that has described the authority and responsibility of each level of manager in the company. The company has carried out budget preparation by classifying controllable and uncontrollable costs, account code classification, and responsibility reports. The implementation of responsibility accounting plays an important role in determining responsibility centers, making it easier for managers to evaluate their performance according to established responsibilities. The performance assessment standard at PT. Semen Indonesia Logistik uses Key Performance Indicators (KPI) that must be achieved within one period.